Hepatic Myxoid Leiomyoma: A Very Rare Tumor - Fraga,João (2020)
Introduction: Mesenchymal tumors of the liver are rare, and in this group, myxoid leiomyomas are even rarer. So far, only 2 cases have been reported in the literature. Case Presentation: We aim to report the case of a 16-year-old female with a large lesion on the right hepatic lobe, grossly composed of gelatinous and heterogeneous tissue. Discussion: Histological evaluation revealed a benign mesenchymal neoplasm with expansive growth, paucicellular, with monotonous and dispersed spindle and ovoid cells, positive for α-smooth actin and h-caldesmon, without atypia or mitoses, consistent with the diagnosis of primary myxoid leiomyoma.